Water quality prediction capabilities of WASP model for a tropical lake system. Issue 4 (December 2015) - Moses, Sheela A.; Janaki, Letha; Joseph, Sabu; Joseph, Justus
Abstract: Water quality modelling facilitates our better understanding of the processes taking place in a lake system, and conservation plans to address them. The water quality analysis simulation programme (WASP) was used in this study to predict daily variations in water quality parameters, namely dissolved oxygen, nitrate, phosphate and chlorophyll‐a and biochemical oxygen demand concentrations in a tropical lake system. The lake was divided into eight segments with the respective morphological, environmental and flow details being model inputs. The monthly concentration of each water quality parameter also comprised model input. The model output was daily spatiotemporal variation in these parameters over a period of 476 days. This study also indicated that the occurrence of precipitation plays a major role in defining the water quality of a tropical lake. The heavy precipitation after a long gap, especially during the summer season, results in a large quantity of organic matter entering the lake through drains, thereby increasing the organic matter and phosphate in the water body, and subsequently resulting in high chlorophyll‐a concentrations in the lake. A reduced chlorophyll‐a concentration was observed during the heavy rains. The water quality fluctuations are more pronounced with precipitation, especially where polluted drains enter the lake. An improved water quality can be observed downstream, including increased dissolved oxygen and nitrate concentrations. Improved water quality was observed during the postmonsoon period, with increased salinity and dissolved oxygen concentrations, a finding that confirms generalized and specific conclusions can be achieved with the use of the WASP model.